Are Changes in Heart Rate Variability in Middle‐Aged and Older People Normative or Caused by Pathological Conditions? Findings From a Large Population‐Based Longitudinal Cohort Study. Issue 2 (February 2016) - Jandackova, Vera K.; Scholes, Shaun; Britton, Annie; Steptoe, Andrew
Abstract : Background: No study to date has investigated longitudinal trajectories of cardiac autonomic modulation changes with aging; therefore, we lack evidence showing whether these changes occur naturally or are secondary to disease or medication use. This study tested whether heart rate variability (HRV) trajectories from middle to older age are largely normative or caused by pathological changes with aging in a large prospective cohort. We further assessed whether HRV changes were modified by socioeconomic status, ethnicity, or habitual physical activity. Methods and Results: This study involved 3176 men and 1238 women initially aged 44 to 69 years (1997–1999) from the UK Whitehall II population‐based cohort. We evaluated time‐ and frequency‐domain HRV measures of short‐term recordings at 3 time points over a 10‐year period. Random mixed models with time‐varying covariates were applied. Cross‐sectionally, HRV measures were lower for men than for women, for participants with cardiometabolic conditions, and for participants reporting use of medications other than beta blockers. Longitudinally, HRV measures decreased significantly with aging in both sexes, with faster decline in younger age groups. HRV trajectories were not explained by increased prevalence of cardiometabolic problems and/or medication use. In women, cardiometabolic problems were associated with faster decline in the standard deviation of all intervals between R waves with normal‐to‐normal conduction, in low‐frequency HRV, and in low‐frequency HRV in normalized units. Socioeconomic status, ethnicity, and habitual physical activity did not have significant effects on HRV trajectories. Conclusions: Our investigation showed a general pattern and timing of changes in indices of cardiac autonomic modulation from middle to older age. These changes seem likely to reflect the normal aging process rather than being secondary to cardiometabolic problems and medication use.